2011
DOI: 10.1002/jcu.20866
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue chondromyxoid fibroma of the foot: Sonographic findings

Abstract: Chondromyxoid fibroma is a rare benign bone tumor, which represents less than 1% of primary bone tumors. However, chondromyxoid fibroma developing in the soft tissue is extremely rare. We report the sonographic findings in a case of soft tissue chondromyxoid fibroma in the foot confirmed pathologically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In the available literature, we found a single publication with a case report of soft tissue HMF removal by Kim et al 5 .…”
Section: Discussionmentioning
confidence: 99%
“…In the available literature, we found a single publication with a case report of soft tissue HMF removal by Kim et al 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Two reports of extremely rare chondromyxoid fibroma of soft tissue have been published. 22,23 However, both were focused on radiographic or sonographic findings, and the histological findings were not elucidated. It might not be necessary to include chondromyxoid fibroma in differential diagnosis at this point, if the tumor is obviously originated from soft tissue without connection to bone.…”
Section: Discussionmentioning
confidence: 99%
“…24 Investigators have reported the extension of the tumor to soft tissue. 25 However, to the best of our knowledge, investigators have described only 2 cases of a primary tumor with no bone involvement. 25,26 In the histologic analysis, soft-tissue chondromyxoid fibroma exhibits a lobular pattern with stellate or spindle-shaped cells on a myxoid or chondroid background.…”
Section: Differential Diagnosismentioning
confidence: 97%